A combined X‐ray crystallography and theoretical study of N—H…OX (X is =P and —C) hydrogen bonds in two new structures with a (C—O)2(N)P(=Y) (Y is O and S) skeleton. Issue 12 (13th November 2018) - Vahdani Alviri, Banafsheh; Pourayoubi, Mehrdad; Farhadipour, Abolghasem; Nečas, Marek; Bertolasi, Valerio
Abstract : The N—H…O hydrogen bonds were studied, both theoretically and experimentally, in two new phosphorus(V)‐based structures. A comparison was made with regard to the O atoms of the P=O or C—O—P groups. Abstract : The crystal structures of N, N ′‐(cyclohexane‐1, 4‐diyl)bis( O, O ′‐diphenylphosphoramide), C30 H32 N2 O6 P2 or (C6 H5 O)2 P(O)(1‐NH)(C6 H10 )(4‐NH)P(O)(OC6 H5 )2, (I ), and N, N ′‐(1, 4‐phenylene)bis( O, O ′‐dimethylthiophosphoramide), C10 H18 N2 O4 P2 S2 or (CH3 O)2 P(S)(1‐NH)(C6 H4 )(4‐NH)P(S)(OCH3 )2, (II ), have been investigated. In the structure of (I ), with an (O)2 (N)P(O) skeleton, two symmetry‐independent phosphoramide molecules are linked through N—H…O=P hydrogen bonds. In the structure of (II ), with an (O)2 (N)P(S) skeleton, the ester O atoms take part in N—H…O—C hydrogen bonds as acceptors; the P=S groups do not participate in hydrogen‐bonding interactions. The strengths of these hydrogen bonds were evaluated, using quantum chemical calculations with the GAUSSIAN09 software package at the B3LYP/6‐311G(d, p) level of theory. For this, LP(O) to σ*(NH) charge transfers were studied, according to the second‐order perturbation theory in natural bond orbital (NBO) methodology, for a three‐component cluster of hydrogen‐bonded molecules for both structures, including all of the independent N—H…O hydrogen bonds observed in the crystal packing. The details of the intermolecular interactions were studied by Hirshfeld surface maps and two‐dimensional fingerprint plots.